Preparation and Development of Polyherbal Natural Hand Sanitizer - Ravina Patidar, Bharat Chouhan (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
The main aim for the preparation of a polyherbal hand sanitizer is for “hand hygiene.” It is a vital principle in the prevention, control, and reduction of any acquired infection. Mainly hand sanitizer can stop the chain of transmission of micro-organisms and other bacteria from hand to different parts of our body. Hand hygiene is important and one of the most critical steps in food production, food service as well as in homes and other day care preparations. Hand sanitizer avoids adverse effects such as itching, irritation, and dermatitis. This study aimed to formulate a polyherbal hand sanitizer using neem, Eucalyptus, and cinnamon extracts and to evaluate its physiochemical parameters, stability, and antimicrobial activity. In conclusion, the formulated Polyherbal hand sanitizer using neem, Eucalyptus, and cinnamon extracts showed good physiochemical parameters, stability, and antimicrobial activity. The use of natural plant extracts in hand sanitizers is a promising alternative to synthetic antimicrobial agents, which may have adverse effects on human health and the environment. Further studies are warranted to evaluate the safety and efficacy of the polyherbal hand sanitizer in humans.